Analisis Kesalahan Penggunaan Huruf Kapital pada Paragraf Deskriptif Siswa Kelas 1 Sekolah Dasar - Fitri Destyana; Marhamah; Puji Ayurachmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the errors in the use of capital letters and punctuation in descriptive paragraphs of grade 1 elementary school students. This study uses a qualitative descriptive research type that aims to describe the findings of errors in the use of capital letters and punctuation in students, namely by studying and analyzing data objectively according to the data found in the field. The sample of this study was class I of SD Negeri 223 Palembang. Where out of 25 students who were asked to rewrite the descriptive text given by the author, it was found that 25 students made errors in the use of capital letters and punctuation. There were 17 students who made errors in writing capital letters in the middle of a sentence, 5 students made errors in writing capital letters at the beginning of a sentence, and 3 students made errors in using capital letters in titles and place names. There were 9 errors in writing period punctuation and 16 students made errors in using comma punctuation. Based on the results of this study, it shows that there are still many students who have difficulty and do not understand the use of capital letters and punctuation correctly and in accordance with the General Guidelines for Indonesian Spelling (PUEBI). This can be caused because during the learning process students are still not focused on receiving information given by the teacher and students are still in the adaptation stage with learning.